Ureteral and / or bladder replacement by silastic-dacron prosthesis in the treatment of invasive cancer of the female genital tract - Corio, Ernesto; Clark, Omar; Campalans, Luis; Rearden, Moisés; Pollero, Héctor; Falconi, Luis (Cirugía del Uruguay, 1977)
We will discuss three cases of ureteral and vesicoureteral invasion, by advanced cancer of the female genitalia. In 'the first' and second observation, due to the extension of the process, an anterior pelvic exanteration was performed, and the lower urinary pole was reconstructed by means óf bilateral ureteral prosthésis, and an external reservoir of Silastic-Dacron. Inmediate good recovery, with normalization of the urinary transit, extremely good physic and psychic acceptance. The first patieht dies within two months from the operation, due to· an acute ischemic cerebrai damage. 'The other patient is leading a good course, now with éight months o' normal life, and normal humoral findings. The third case, is a patient 25 years old, operated from a ieft ovary tumor, Wich presents five year later with a big pelvic tumor, complicated with a bilateral hydronephrosis, with eárly signs of renal function impairment. The tumoral mass was removed, the left ureter was liberated, and an ureteral valved prosthesis of Silastic- Dacron, was placed between ureter and bladder, thus offering the patient a paliative help to this extremely severe complication. The follow-up, one year and half after, reveals normal humoral findings and a good psycophysic adaptatión to this new condition.